Refleksja o kiczu architektonicznym. Iluzja czy namiastka szczęścia? - Stec, Barbara (Załącznik Kulturoznawczy, 2023)
The reflection in this article is focused on the kitsch in architecture. The term ‘kitsch’ itself, originally referred to the images, is nowadays also used for the evaluation of architecture, especially in terms of its authenticity. This requires taking into account the physical scale associated with the function important in architecture, that is, the one of satisfying the needs of its user. What served as a starting point for reflection was the thought of Kurt W. Forster, in which he identified kitsch, including the architecturalone, with the illusion of a better life, inherent in the dream and desire of a man, and constituting the cause of architectural borrowings.It was noted that in architecture, because of its scale and utility, the illusion cannot replace the real fulfillment of the user’s life needs, so it may exist for a relatively short period of time so as to lead to the emergence of its form, or, in the long run, it may subsist next to reality as a useless dummy, excluded from the function of satisfying the needs of the user. Such a kitsch can be seen in architecture, in which a man lives for such a short time that he or she does not need to meet one’s needs based on kitsch.The prolonged use of architectural kitsch deepens in a man a feeling of sadness and irritation resulting from a sense of inability to fulfill dreams or real needs. And if the illusion is only a cause of the architecture – since it disappears into its realized form, borrowed, but useful (as theatre decoration, by meeting the needs of beauty or a multi-sensory experience of architecture) – then you cannot talk about the architectural kitsch, understood as an illusion. Accordingly, the ornament also need not be kitsch if it converts the illusion into a bit of happiness.